Penerapan Perbaikan Mutu Berkelanjutan (Continous Quality Improvement) Pasca Akreditasi Puskesmas Kota Kupang terhadap Tingkat Kepuasan Masyarakat - Manafe, Ovlian Afri; Ratu, Jacob M.; .Muntasir, Muntasir; Roga, Andrias Umbu; Littik, Serlie K. A. (Journal of Telenursing (JOTING), 2023)
This research aims to analyze the effect of implementing continuous quality improvement (Continuous Quality Improvement) through improving the quality of administration and management, performance targets for public health efforts, and improving clinical quality and patient safety (PMKP) after accreditation of community health centers on the level of community satisfaction. The research method used is quantitative observational analytical research using a cross-sectional study. The research results show that Continuous Quality Improvement significantly affects the Level of Community Satisfaction. This can be seen from the significance value of 0.000 0.05; the Fcount value is greater than the FTable value (315.333 3.127). Conclusion: Continuous Quality Improvement (CQI) simultaneously or together influences community satisfaction. Continuous Quality Improvement (CQI) by the Oesapa Community Health Center and Penfui Community Health Center by implementing Community Health Center Accreditation standards significantly affects the level of community satisfaction. Keywords: Community Satisfaction, Continuous Quality Improvement, Community Health Center